Small size sampling? - Pathak, Rakesh R. (International Journal of Basic & Clinical Pharmacology, 2017)
Though small size samples can be planned and justified based on scarcity of time, money and manpower, there are situations making more accuracy a must and needing larger samples sizes. That’s why rare adverse drug reactions are identified only after a drug comes into the market and a large population is exposed to it. There are many more reasons for increasing the sample size and requirement of the study decides which criteria of accuracy should be tightened the most (e.g. avoiding type I error is more important or type II error).